Analysing the impacts of free cash flow, agency cost and firm performance in public listed companies in Malaysia - Noraina Mazuin, Sapuan; Norwazli, Abdul Wahab; Muhammad Ashraf, Fauzi (Penerbit Universiti Malaysia Pahang, 2021)
This study intended to examine the relationship between free cash flow and agency costs towards firm performance based on the data from 350 public listed companies in Malaysia. The data was collected from year 2005 to 2015. There is a need to re-examine the free cash flow hypothesis and the agency theory based on Malaysian data as the results from previous studies shown a mix results. The findings shown free cash flow is significantly giving positive impact on firm performance. This result is contradicting to free cash flow hypothesis, but it can occur due to, when the availability of investments opportunities that can be generated when firm more free cash flow that later able to increase firm performance. Meanwhile, total asset turnover has a positive impact on return on asset. However, the operating expenses ratio demonstrates that the operating expenses ratio has a negative impact on return on asset. The mix findings of agency cost are supported by previous studies.